Les Chirurgiens de la Marine française : des « acteurs vecteurs » de la circulation des savoirs médicaux entre la France et le Rio de la Plata (1838-1852) - Nancy González Salazar; Christine Théré (Les Cahiers ALHIM)
The journey made by six surgeons of the French Navy in the Rio de la Plata during the blockade of Buenos Aires and the Guerra Grande is the common thread through which this article seeks to highlight the medical reality of La Plata during these years of political struggle, as it was apprehended by members of a foreign medical corps. The observations of these surgeons, which gave rise to the writing of doctoral theses situated halfway between the medical topographies and the end-of-campaign medical report that it was their duty to submit at the end of their stay, place climatology at the heart of their work. But they also reflect the links forged between these individuals and the local medical profession and civil society, thus revealing what the various medical exchanges resulting from their stay in La Plata were like.